2017
DOI: 10.1016/j.str.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Effective Microfluidic Spraying-Plunging Method for High-Resolution Single-Particle Cryo-EM

Abstract: Summary We describe a spraying-plunging method for preparing cryo-EM grids with vitreous ice of controllable, highly consistent thickness using a microfluidic device. The new polydimethylsiloxane (PDMS)-based sprayer was tested with apoferritin. We demonstrate that the structure can be solved to high resolution with this method of sample preparation. Besides replacing the conventional pipetting-blotting-plunging method, one of many potential applications of the new sprayer is in time-resolved cryo-EM, as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 54 publications
0
97
0
Order By: Relevance
“…To overcome these limitations and develop a general time-resolved sample preparation method for cryo-EM (trEM) requires building a miniaturized mixer and bioreactor able to rapidly initiate and synchronize biochemical reactions, followed by spreading the incubated sample onto a cryo-EM grid without the need for manual operation or blotting, collectively faster than the lifetime of the structures of interest 19 . Previous work has shown that combining reactants in microfluidic devices followed by rapid application of sample by gasassisted spraying is in principle possible [20][21][22][23][24][25] , and has yielded fascinating new insights into biology 26 . However, substantial technical challenges remain unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations and develop a general time-resolved sample preparation method for cryo-EM (trEM) requires building a miniaturized mixer and bioreactor able to rapidly initiate and synchronize biochemical reactions, followed by spreading the incubated sample onto a cryo-EM grid without the need for manual operation or blotting, collectively faster than the lifetime of the structures of interest 19 . Previous work has shown that combining reactants in microfluidic devices followed by rapid application of sample by gasassisted spraying is in principle possible [20][21][22][23][24][25] , and has yielded fascinating new insights into biology 26 . However, substantial technical challenges remain unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated by the ground-breaking work on the acetyl choline esterase receptor 11 . Alternatively, in a 'mix and spray approach substrate and protein can be pre-mixed in a microfluidic chamber, before directly spraying onto a fast-moving EM grid, which is plunged into liquid ethane 12,13 . This technique has shown great promise for studies of ribosome mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…To improve sample deposition on EM grids, several developments have been presented, including droplet-based methods [20][21][22][23][24] , e.g. on nanowire grids 25 , and using capillaries followed by sample thinning by controlled water evaporation 26 .…”
Section: Pin Printingmentioning
confidence: 99%